System controls of coastal and open ocean oxygen depletion. (September 2021) - Pitcher, Grant C.; Aguirre-Velarde, Arturo; Breitburg, Denise; Cardich, Jorge; Carstensen, Jacob; Conley, Daniel J.; Dewitte, Boris; Engel, Anja; Espinoza-Morriberón, Dante; Flores, Georgina; Garçon, Véronique; Graco, Michelle; et al.
Highlights: The epoch of the Anthropocene, a period during which human activity has been the dominant influence on climate and the environment, has witnessed a decline in oxygen concentrations and an expansion of oxygen-depleted environments in both coastal and open ocean systems since the middle of the 20th century. This review paper provides a synthesis of system-specific drivers of low oxygen in a range of case studies representing marine systems in the open ocean, on continental shelves, in enclosed seas and in the coastal environment. Identification of similar and contrasting responses within and across system types and corresponding oxygen regimes is shown to be informative both in understanding and isolating key controlling processes and provides a sound basis for predicting change under anticipated future conditions. Case studies were selected to achieve a balance in system diversity and global coverage. Each case study describes system attributes, including the present-day oxygen environment and known trends in oxygen concentrations over time. Central to each case study is the identification of the physical and biogeochemical processes that determine oxygen concentrations through the tradeoff between ventilation and respiration. Spatial distributions of oxygen and time series of oxygen data provide the opportunity to identify trends in oxygen availability and have allowed various drivers of low oxygen to be distinguished through correlative and causative relationships. Deoxygenation results from a complex interplay of hydrographic and biogeochemical processes and the superposition of these processes, some additive and others subtractive, makes attribution to any particular driver challenging. System-specific models are therefore required to achieve a quantitative understanding of these processes and of the feedbacks between processes at varying scales. Abstract: The epoch of the Anthropocene, a period during which human activity has been the dominant influence on climate and the environment, has witnessed a decline in oxygen concentrations and an expansion of oxygen-depleted environments in both coastal and open ocean systems since the middle of the 20th century. This paper provides a review of system-specific drivers of low oxygen in a range of case studies representing marine systems in the open ocean, on continental shelves, in enclosed seas and in the coastal environment. Identification of similar and contrasting responses within and across system types and corresponding oxygen regimes is shown to be informative both in understanding and isolating key controlling processes and provides a sound basis for predicting change under anticipated future conditions. Case studies were selected to achieve a balance in system diversity and global coverage. Each case study describes system attributes, including the present-day oxygen environment and known trends in oxygen concentrations over time. Central to each case study is the identification of the physical and biogeochemical processes that determine oxygen concentrations through the tradeoff between ventilation and respiration. Spatial distributions of oxygen and time series of oxygen data provide the opportunity to identify trends in oxygen availability and have allowed various drivers of low oxygen to be distinguished through correlative and causative relationships. Deoxygenation results from a complex interplay of hydrographic and biogeochemical processes and the superposition of these processes, some additive and others subtractive, makes attribution to any particular driver challenging. System-specific models are therefore required to achieve a quantitative understanding of these processes and of the feedbacks between processes at varying scales.